Field assessment of the impacts of Deepwater Horizon oiling on coastal marsh vegetation of Mississippi and Alabama. (18th July 2016) - Willis, Jonathan M.; Hester, Mark W.; Rouhani, Shahrokh; Steinhoff, Marla A.; Baker, Mary C.
Abstract: The Deepwater Horizon incident, which occurred in April 2010, resulted in significant oiling of coastal habitats throughout the northern Gulf of Mexico. Although the most substantial oiling of coastal salt marshes occurred in Louisiana, oiling of salt marshes in Mississippi and Alabama was documented as well. A field study conducted in Mississippi and Alabama salt marshes as a component of the Deepwater Horizon Natural Resource Damage Assessment determined that >10% vertical oiling of plant tissues reduced live vegetation cover and aboveground biomass (live standing crop) relative to reference sites in this region through fall 2012. This reduction of live vegetation cover and aboveground biomass appears to have largely resulted from diminished health and vigor of Juncus roemerianus, a key salt marsh species in Mississippi and Alabama. Fewer significant reductions in live vegetation cover and aboveground biomass were detected by the fall 2013 sampling, suggesting that vegetation in oiled salt marshes in this region may have begun to recover. This is corroborated by low levels of Deepwater Horizon oil contamination in these salt marsh soils. However, these findings should be interpreted in the context of the restricted sampling intensity of the present study. Environ Toxicol Chem 2016;35:2791–2797. © 2016 The Authors. Environmental Toxicology and Chemistry Published by Wiley Periodicals, Inc. on behalf of SETAC.